Loan to Deposit Ratio dan Biaya Operasional Pendapatan Operasional Terhadap Kinerja Keuangan Industri Perbankan di Indonesia - Eriana Zahra (Jurnal Dinamika Ekonomi & Bisnis, 2022)
The IDX 30 indexed banks are the banks with the largest market capitalization values and are often referred to as bluechip stocks. So this research has the aim to see the effect of LDR and BOPO on Financial Performance. The research data is obtained from the bank's annual report. The method used is multiple linear regression analysis. The results of this research Loan Deposit Ratio partially does not affect financial performance. Meanwhile, Operating Costs, Operating Income, affect Financial Performance